STRATEGI PENGELOLAAN LAHAN GAMBUT EKS HGU BERBASIS MASYARAKAT DI KECAMATAN PUSAKO KABUPATEN SIAK - Dudi Candra; Suwondo Suwondo; Sofyan Husein Siregar (Program Pascasarjana Universitas Riau, 2020)
Central government authority which governing mastery, ownership, use and utilization of land and natural resources sectorally, authoritarian, and centralized in granting licenses for utilization of natural resources to business entities resulting in 3 (three) main problems, that are land tenure inequality, agrarian conflicts in natural resource management, and environmental damage. In 2018 in Riau Province, precisely in Siak Regency, Government implements land redistribution exconcession (HGU) of PT. Mahakarya Eka Guna (MEG) for community through the land objected of agrarian reform program (TORA) in order to rearrange the imbalance of mastery structure, ownership, use and utilization of land toward which more fair. So that land can be a source of livelihood and welfare for the community. TORA Program location is majority are in the function area of the peat swamp ecosystem Ministry of Environment and Forestry (KLHK) with peat depths of more than 3 meters, so the management of peatlands must follow government regulations related to regional function. The condition is currently being carried out land clearing on the exconcession land in TORA program to immediately utilization land, while the public does not have enough information and knowledge about the most profitable choice of plants.